Major diet of common carp (Cyprinus carpio L.) over different developmental stages in rice-field: Agroecological interactions between fishes and rice in Sichuan, China, based on DNA metabarcoding approach - Mengling Wu; Ruisen Lu; Wenhao Huang; Hongyi Liu; Yan Zou; Ling Tao; Yun Sun; Qiong Wang; Keyi Tang (Global Ecology and Conservation)
The rice-fish co-culture system (RFS) is a traditional cooperative farming model employed in southern China that can achieve doubling the harvest of rice (Oryza sp.) and fish. Most studies on RFS have focused on ecological mechanisms, benefits, ecosystem services, and agroecosystem functions; however, little is known about the baseline dietary composition in common carp of RFS, particularly across different developmental stages. In this study, we applied DNA metabarcoding of invertebrates (COI) and plants (Rbcl) to investigate the natural diets of common carp (Cyprinus carpio) across three developmental stages: juvenile (May), sub-adult (July), and adult (September). The animal-derived diets of common carp were dominated by prey from the orders Diptera, Lepidoptera, and Hemiptera, and the main plant-derived food items belonged to the families Poaceae, Araceae, and Hydrocharitaceae. We examined variations in the dietary compositions of common carp across three developmental stages to capture adaptations to seasonal changes in food resource availability. Additionally, we detected insect pests (species from the genera Macrosteles and Mythimna) and weeds (Eleusine indica, Alternanthera philoxeroides, Mazus japonicus, and Poa annua) in the diets of common carp, confirming the ecological benefits of common carp in rice fields by reducing insect pests and weeds. Characterizing the dietary composition and variation of common carp over developmental stages contributes to our understanding of its foraging ecology, dietary niche, and dynamics of trophic interactions, and provides critical information for evaluating the ecological benefits of common carp in RFS.